ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU PERPINDAHAN PELANGGAN - Romadhon, Gilang (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
With the increasing number ofbeauty clinics in last three years, beauty clinic customer shave more optionsandhave the opportunity to switch from one beauty clinic to another beauty clinic. The purpose of this study is to analyze factor sthataffect customer switching behavior and find the dominant factor that influences this behavior. This study utilizes a descriptive research design. Primary data were collectedby distributing questionnairesto a sample of 150 respondents. The population in this study is all beauty clinics customers in Malang City. Multiple linear regression analysis was performed to analyze the data. The result of this study reveals thatprice, advertising, products, commitment, sales promotion, physical place of business environment (location), service, satisfaction, and reputation influence customer decision to switch to another beauty clinicspartially as well as simultaneously. The result finds that amongst those variables, price is the dominant factor influencing customer switching behavior. Some recommendation towards beauty clinic are then suggested. Key words: switchingbehavior, beauty clinics, regression analysis.